Critical Reading Skills in English of Incoming Grade 10 Learners: An Analysis and Interpretation - Tan, Helen Suelto (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Critical reading encourages students to think more deeply and actively to understand a reading material. It is a manner of broadening one's mind and enhancing their thought process. The study analysed the critical reading skills of Grade 9 students and assessed the difficulties they encountered to shed light and provide valuable solutions in the successful development and improvement of the students critical reading skills. The study utilized a qualitative research design involving Grade 9 learners and English teachers who are employed in a public high school in the Philippines. Data were gathered through the use of semi-structured survey questionnaires, both for Grade 9 learners and teachers. In this study, the researcher used a purposive sampling technique to select the three Grade 9 students, and three English teachers who became part of the study. The findings revealed that students' perception of their reading ability is below average. The majority of the respondents have poor reading skills. In addition to these, students have limited vocabulary and often disassociate themselves to reading. The different strategies used in motivating students to read were presented. The majority of the teacher respondents stated that critical reading skills are part of higher-order thinking skills. Moreover, a shortage in teaching facilities and resources in the classroom are the major factors why students have poor reading ability. Findings revealed that the majority of the teacher respondents claimed that improving critical reading skills of the students can also enhance their reading comprehension skills.